2008
DOI: 10.1016/j.yqres.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Orbital- and sub-orbital-scale climate impacts on vegetation of the western Mediterranean basin over the last 48,000 yr

Abstract: High-resolution pollen analysis of Alborán Sea core MD95-2043 provides a 48-ka continuous vegetation record that can be directly correlated with sea surface and deep-water changes. The reliability of this record is supported by comparison with that of Padul (Sierra Nevada, Spain). Marine Isotope Stage (MIS) 3 was characterised by fluctuations in Quercus forest cover in response to Dansgaard-Oeschger climate variability. MIS 2 was characterised by the dominance of semi-desert vegetation. Despite overall dry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
263
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 345 publications
(311 citation statements)
references
References 72 publications
43
263
4
1
Order By: Relevance
“…4) as shown by the progressive decrease in natural forest species and the increase in xerophytes such as Artemisia. This agrees with previous 15 paleoclimatic studies in the western Mediterranean, which document a progressive aridification trend since ~7000 cal yr BP (Carrión et al, 2002;Fletcher and Sánchez Goñi, 2008;Jalut et al, 2009;Carrión et al, 2010;Anderson et al, 2011;Jiménez-Moreno et al, 2012. Jiménez- Moreno et al ( , 2015 suggested that semidesert expansion and Mediterranean forest decline during the late Holocene in this area could be explained by decreasing summer insolation (Laskar et al, 2004;Fig.…”
Section: Aridification Trend During the Late Holocenesupporting
confidence: 91%
“…4) as shown by the progressive decrease in natural forest species and the increase in xerophytes such as Artemisia. This agrees with previous 15 paleoclimatic studies in the western Mediterranean, which document a progressive aridification trend since ~7000 cal yr BP (Carrión et al, 2002;Fletcher and Sánchez Goñi, 2008;Jalut et al, 2009;Carrión et al, 2010;Anderson et al, 2011;Jiménez-Moreno et al, 2012. Jiménez- Moreno et al ( , 2015 suggested that semidesert expansion and Mediterranean forest decline during the late Holocene in this area could be explained by decreasing summer insolation (Laskar et al, 2004;Fig.…”
Section: Aridification Trend During the Late Holocenesupporting
confidence: 91%
“…The freshwater glacial melt release and AMOC shutdown leave a clear climatic fingerprint on the Iberian Peninsula during stadial events of T-I and MIS 3 because weakened heat transport shifted storm tracks and led to extremely dry conditions (21,22). This connection results from the expansion of the polar vortex during AMOC shutdowns, which lead to the southward arrival of polar or continental air outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…4) was obtained employing standard methods of pollen extraction, identification and counts reported in Fletcher and Sanchez Goñi (2008 (Fig. 4).…”
Section: Pollen Datamentioning
confidence: 99%
“…5) reveals a long-term recovery of forest populations across the last glacial-interglacial transition, with minimum values (<10%) during the H1 interval (as defined on the basis of marine climatic tracers in the same core (Cacho et al, 2006(Cacho et al, , 1999Fletcher and Sanchez Goñi, 2008)), intermediate values (15-50%) during the Lateglacial and Preboreal (PB), and high values (>50%) after 10.6 cal ka BP. Following the expansion of forest populations at the end of H1, discrete intervals of reduced forest development are detected (in all cases by the values of at least two samples) throughout the Lateglacial and early Holocene, centred on 14.…”
Section: Variability In Temperate Mediterranean Forestmentioning
confidence: 99%
See 1 more Smart Citation